ANALISIS PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Azzahra, Fitri Amalia; Sutanto, Aftoni (Jurnal Fokus Manajemen Bisnis, 2016)
This study is entitled Analysis of the Effect of Financial Financial Ratios on Stock Returns on Consumer Goods Companies Listed on the Indonesia Stock Exchange in 2012-2014. The purpose of this study is to determine whether the variable Current ratio (CR), Debt to Equity Ratio (DER), Earning per Share (EPS), and Total Asset Turn Over (TATO) affect the stock return. The analytical tool used is multiple linear regression, t test, F test, and R2. T test results prove that the CR variable has no effect on stock returns with a probability value of 0.9755, the DER variable has no effect on stock returns with a probability value of 0.9442, the EPS variable has an effect on stock returns with a probability value of 0.0049, and TATO has no effect on stock returns with a probability value of 0.9809. The test results with the F test prove that the variables CR, DER, EPS, and TATO simultaneously have no effect on stock returns with a probability value of 0.050589. The R2 test result, 0.278689, shows that the dependent variable of stock returns can be explained by the independent variables CR, DER, EPS, and TATO by 27.8% while the remaining 72.2% is explained by other variables not examined in this study.